Biological, demographic, and health factors associated with HPV infection in Ecuadorian women - Roman, Carlos; Andrade, Diego; Hernández, Yenima; Salazar, Zoila K.; Espinosa, Lizette; Campoverde, Erika; Guallaizaca, Lourdes; Merchán, María; Sarmiento, Miriam; Brenner, Jonathan (Frontiers in Public Health, 2023)
Objectives: The study aims to identify the correlation between HPV infection and sociodemographic and sexual reproductive health in Ecuadorian women from March to August 2019. Methods: 120 women were randomly selected from two gynecological clinics to complete a questionnaire and provide a biospecimen. PCR-Hybridization did genotype of 37 HPV serotypes in samples obtained by endo-cervical brushing for liquid base cytology. Sociodemographic and sexual health data were collected through a validated questionnaire in a medical consultation. Mathematical modeling of HPV infection was done using bivariate logistic regression. Results: 65% of the women sampled had an HPV infection; 74.35% of these women had co-infections. Out of the women who were HPV positive, 49.1% were diagnosed with high-risk genotypes from HPV strains 18, 35, 52, and 66. Parity, immunosuppression, and use of oral contraception / IUD were identified as associated variables. The explanatory model had a sensitivity of 89.5% and a specificity of 73.8%. Conclusions: The predominant strains of HPV among Ecuadorian women are diverse. Diagnosis of HPV risk infection is a complex phenomenon where biological and psychosocial variables are integrated into a model. HPV infection screening requires new alternatives depending on the country. HPV screening in populations with limited access to health services, low socioeconomic status, and negative sociocultural beliefs about STIs must use surveys as a step before screening for HPV infections. Future research should probe the diagnostic value of HPV screening surveys in Ecuadorian women with a higher and more diverse population.